Pengaruh Media Sosial Terhadap Gaya Hidup Remaja - Ari Asmawati; Adinda Firdhiya Pramesty; Tasya Restiatul Afiah (UNIVERSITAS RAHARJA, 2022)
Social media is growing rapidly because everyone is able to have social media such as Instagram. The existence of social media for teenagers has made it easier for them to better understand the outside world, such as interactions between individuals and groups. However, the presence of social media has led to negative behavior towards adolescent lifestyles, making adolescents appear more individualistic, thus immediately triggering a lack of awareness of the desired environment. Inappropriate use of social media can damage relationships between individuals and groups. According to initial observations, many teenagers are using gadgets and are active as social media users, some of whom want to see their luxurious lifestyle on social media. Social media seems to be a basic need in the daily lives of teenagers. Most teenagers tend to upload photos that show extravagant (hedonistic) and arrogant behavior, which can damage teenagers' social relationships. In this discussion, the authors aim to present the findings of a study on the impact of social media users on adolescent lifestyles. The author uses qualitative research methods and uses google form media as a data collection technique. Keywords—Media; Social; Teenager Media sosial berkembang dengan pesat dikarenakan setiap orang mampu mempunyai media sosial seperti Instagram. Adanya media sosial bagi remaja telah memudahkan mereka untuk lebih memahami dunia luar, seperti interaksi antar individu maupun kelompok. Namun, kehadiran media sosial telah memunculkan perilaku negatif terhadap gaya hidup remaja, membuat remaja tampil lebih individualistis, sehingga segera memicu sikap kurang kesadaran terhadap lingkungan yang diinginkan. Penggunaan media sosial yang tidak tepat dapat merusak hubungan antara individu dan kelompok. Menurut pengamatan awal, banyak remaja yang menggunakan gadget dan aktif sebagai pengguna media sosial, beberapa di antaranya ingin melihat gaya hidup mewah mereka di media sosial. Media sosial seolah menjadi kebutuhan pokok dalam keseharian remaja. Kebanyakan remaja cenderung mengunggah foto yang menunjukkan perilaku boros (hedonistik) dan arogan, yang dapat merusak hubungan sosial remaja. Dalam pembahasan ini, penulis bertujuan memaparkan temuan dari studi tentang dampak pengguna media sosial terhadap gaya hidup remaja. Penulis menggunakan metode penelitian kualitatif dan menggunakan media google form sebagai teknik pengumpulan data. Kata Kunci—Media; Sosial; Remaja